Auditoria del área administrativa financiera para el control de la inversión económica en la compra de bienes de la empresa comercial casanova de Cantón El Empalme 2009-2010 - Palma Tuarez, Linda Grace (2012)
Thisprojectis aimed atcarrying outan auditof thefinancialadministrative areaCasanovaCommercialCompanyduringthe period 2009-2010, to identifythe degree ofefficiency, effectiveness andthe shortcomingsin the processesofinvestmentand procurement of goods. TheCommercialCasanovaislegally registeredwith the Superintendency ofCompanies, was established onFebruary 22, 1995, with an initial capitalof $100,000,000 (sucre), equivalent toUSD4000. Casanovatrading companyis an entity createdfor profitandoperatesagriculturalproduct line. Theinvestments madeareverystrongamountsandthe controls are veryflexible. The work ofsearchand data collectionwasbased onmethodsand techniquesofscientific research underthefinancialmanagement auditapproach, such as observation, interviews, document analysissurvey, thusconfirmedandconfirmed thehypothesis. The auditcarriedoutallowed to discoverwhat were themost criticalflawsinqthe company must takecorrective. Theadministrativeentity needsfinancialauditthusbetter managetheir investmentsand management. The fundamental thingworth notingonthe auditafterit was evidentthe lackof organization and controlwithinareadministrative. Also the lack ofinvestment studythatthreatens thecommercialeconomy. This companyis runby CarlosCasanova. andis engaged in thepurchase andsale of agricultural products